Asphalt pavement temperature prediction - Minhoto, Manuel (2010)
A 3-D finite element model (FEM) was developed to calculate the lemperature of an asphtalt rubber pavement localed in the Northeast of Portugal. The goal of the case study presented in this paper is to show the good accuracy temperature prediction tha can be obtained with this model when compared with the field pavement thermal condition obtained during a year. lnput data to the model are the hourly values for solar radiation and temperature and the mean daily value of wind speed obtained from a meteorological station. The therminal response of a multilayered pavement structure is modelled using a FEM transient thermal analysis and each analysis was initiated with the full deph constant initial temperature abtained from field measurements. For each analysed day, the pavement temperature was measured at a new pavement section, located in IP4 main road, near Bragança, in the north of Portugal. At this location, seven thermocouples were installed in the asphalt rubber and conventional mix layer, at seven different depths. These paviment data was used to validate this simulation model, by comparing model calculated data with mesured pavement temperatures. As conclusion, the 3-D finite-element analysis proved to be an interesting tool to simulate the transient behavior of the asphalt pavements. The presented simulation model can predict the pavement temperature at diferrent levels of bitumious layers with good accuracy.